Limited agency, racialized labor, and the mechanization of Asian international students in U.S. higher education - Siddiqui, Shan Mohammed (Journal of International Students, 2026)
Over 1 million international students work in U.S. institutions of higher education, with the majority being from Asia. Although previous scholarship has emphasized the cultural and language barriers faced by this population, relatively little is known about the labor conditions of these students and how they may contribute to inequality. Utilizing Bui’s concept of Asian roboticism and literature on racial capitalism, this study investigates the working conditions of Asian international students in various disciplines across the U.S. Drawing on 22 in-depth interviews, the findings revealed three major themes: 1) limited agency in making decisions, 2) racialized labor driven by the model minority myth, and 3) the mechanization of Asian bodies. These conditions negatively affect students’ mental health, physical health, and social well-being. The results underscore the harm perpetuated by racial stereotypes about Asian workers and highlight directions for future research on inequality in higher education.